Methods And Significance Of Checking The Knowledge Of Students In The Educational Process In Mathematics Lessons - Munisa Aminovna Davlatova (Euro Asian Journal Publishing, 2024)
The article talks about the importance of checking students' knowledge in the educational process in elementary mathematics classes, as well as verbal and calculation methods
Keywords: Student; teacher; memory